Aprendizagem baseada em projetos: uma ferramenta elementar para o desenvolvimento da Educação Integral - Sá, Carolina Castellan Ferreira de (Universidade do Vale do Rio dos Sinos, 2019)
This article’s main theme is “project based learning” (PBL). The work developed here, seeks to analyze in which way this learning methodology contributes to the integral development of the individual, appreciating it as an active subject of the learning process. We will also highlight, which the main features of the PBL and the times and spaces in which it can be applied. With this purpose, we present a project experience performed with a 4th and 5th grades class, in a private school in the city of São Paulo, pointing out the findings made and the results achieved after a reflection and analysis of the process
Keywords: Aprendizagem baseada em projetos; Educação integral; Desenvolvimento; Project based learning; Integral education; Development